Stress and Coping Among Medical Officers in Kerala: A Cross-sectional Study (Kerala Journal of Psychiatry, 2018)
Background: There is strong evidence to suggest that medical practitioners experience high levels of stress and it affects their work performance and quality of medical care. Adaptive and maladaptive coping strategies can influence the extent and severity of stress. However, empirical studies examining stress and coping among medical practitioners are less from Kerala.Methods: Using a cross-sectional research design, we examined stress and coping among 31 medical officers in Kerala. The participants were recruited during the annual meeting of Kerala Government Medical Officers Association (KGMOA) held at Nilambur. Perceived Stress Scale and Brief Cope Inventory were used to measure their stress and coping. Descriptive and bivariate analysis were used to interpret the data.Results and Discussions: Participants experienced moderate level of stress. The stress was significantly correlated with denial (r=.646), substance use (r=.667), use of emotional support (r= -.674) use of instrumental support (r= -.612) positive reframing (r= -.510) and planning (r= -.459).Conclusion: Future studies may examine the predictive validity of the identified coping variables in a large sample. It is highly recommended that stress management and coping skill training programmes be organized for the medical officers in Kerala.
Keywords: stress; coping; medical officers